Improving punching behavior of interior voided slab-column connections using steel sheets. (15th November 2019) - Al-Gasham, Thaar S.; Mhalhal, Jasim M.; Jabir, Hussain A.
Highlights: A new method for improving punching strength of voided slabs was presented. The punching behavior of slabs was investigated experimentally and numerically. Introducing voids inside the slabs remarkably influenced their responses. The proposed method was excellent in improving an overall behavior of voided slabs. The efficiency of sheets increased with augmenting their thickness. The sheets were more active when they placed below or near the column stub. Abstract: In recent modern buildings, voided slabs have been extensively employed because of the high reduction in their self-weight up to 35%. Limited studies have been conducted on such slabs, and no significant drop in the flexural strength was reported due to introducing voids. In contrast, a considerable drop in the punching strength of the voided slabs was addressed. Therefore, this study presented a new and simple method for improving the punching shear strength and behavior of such slabs by employing steel sheets. Five half-scale specimens were fabricated. One slab was solid and kept as a reference specimen, while the others were voided slabs. They contained 96 spherical voids distributed uniformly throughout the slab area, three of them were strengthened by six embedded steel sheets, three sheets in each direction. The sheets were orthogonally configured and intersected below the column stub. The variable of the study was the sheet thickness (0.8 mm, 1.0 mm, and 1.2 mm). The specimens were subjected to a gradually concentrated load through the column up to collapse. The test results revealed that significant losses were recorded in the strength, stiffness, ductility, and energy absorption of the voided slab without sheets compared with the reference one. However, the strengthening of voided slabs by sheets was superior not only in retrieving these losses but also in exceeding them. Besides, FE analysis was conducted, utilizing the ABAQUS program, for profoundly illustrating the experimental findings and performing a parametric study. Based on the FE observations, the activation of sheets was found to be increased by enlarging their thickness, and the best activation was observed when gathering the sheets below or nearer the column stubs.